THE ESSENCE AND EVOLUTIONARY DEVELOPMENT STAGES OF INTELLIGENT MANUFACTURING SYSTEMS - Donaeva Feruza Burkhon qizi (Ecomind Press, 2025)
This in the article smart working release The essence of AIChT systems and their evolutionary development stages analysis Technological from paradigms starting , artificial intelligence , IoT, big information and cognitive calculation systems to industry integration through AIChT's step by step development statement Also , Uzbekistan 's " Digital "Uzbekistan - 2030" strategy based on this systems national in the economy implementation to grow prospects Historical and modern of scientists theory based on , AIChT working release efficiency increase , flexibility reinforcement and innovative potential to form focus proving International strategies analysis , scientific research and Uzbekistan in the example of practical directions deep seeing released.
Keywords: Smart working release systems; digital transformation; artificial intellect; Industry 4.0; innovative industry; automation; Uzbekistan 2030 strategy.